Clinical outcomes of therapeutic approaches to subclinical hypothyroidism: An integrative review (Research, Society and Development, 2023)
Subclinical hypothyroidism is characterized by high levels of thyroid-stimulating hormone in addition to normal levels of free thyroxine. Patients need to be monitored in order to find the most effective clinical and therapeutic approach for each individual. The most commonly used therapeutic approach is levothyroxine, which has no clear evidence of its benefits. Therefore, this study is an integrative literature review, which aim to synthesize the studies related to the possible benefits or not of using levothyroxine in the therapeutic approach to subclinical hypothyroidism, evaluating various clinical aspects. The MEDLINE (via PubMed), EMBASE and SCIELO databases were included in the search, focusing on original articles, especially randomized clinical trials in English and Spanish, covering the last 5 years, including 2023. From the results, it was possible to discuss clinical outcomes related to the cardiovascular, musculoskeletal and hematopoietic systems, as well as psychiatric manifestations and effects on laboratory aspects. In addition, other therapies for managing the disease were discussed. The analysis made shows that levothyroxine replacement does not present significant results for the treatment of subclinical hypothyroidism, as well as the other therapeutic options discussed.